CTX-M extended-spectrum β-lactamase-producing Klebsiella spp, Salmonella spp, Shigella spp and Escherichia coli isolates in Iranian hospitals - Bialvaei,Abed Zahedi (2016)
Abstract This study was conducted in Iran in order to assess the distribution of CTX-M type ESBLs producing Enterobacteriaceae. From January 2012 to December 2013, totally 198 E. coli, 139 Klebsiella spp, 54 Salmonella spp and 52 Shigella spp from seven hospitals of six provinces in Iran were screened for resistance to extended-spectrum cephalosporins. After identification and susceptibility testing, isolates presenting multiple-drug resistance (MDR) were evaluated for ESBL production by the disk combination method and by Etest using (cefotaxime and cefotaxime plus clavulanic acid). All isolates were also screened for bla CTX-M using conventional PCR. A total of 42.92%, 33.81%, 14.81% and 7.69% of the E. coli, Klebsiella spp, Salmonella spp and Shigella spp isolates were MDR, respectively. The presence of CTX-M enzyme among ESBL-producing isolates was 85.18%, 77.7%, 50%, and 66.7%, in E. coli, Klebsiella spp, Salmonella spp and Shigella spp respectively. The overall presence of CTX-M genes in Enterobacteriaceae was 15.4% and among the resistant isolates was 47.6%. This study indicated that resistance to β-lactams mediated by CTX-M enzymes in Iran had similar pattern as in other parts of the world. In order to control the spread of resistance, comprehensive studies and programs are needed.